2011
DOI: 10.1109/tmag.2011.2157997
|View full text |Cite
|
Sign up to set email alerts
|

Picotesla Magnetic Sensors for Low-Frequency Applications

Abstract: We demonstrate a simple low-power, magnetic sensor system suitable for high-sensitivity magnetic-field mapping, based on solid-state magnetic tunnel junction devices with minimum detectable fields in a 100 pT range at room temperature. In this paper, we discuss a method that uses multilayer thin films to improve the performance of the soft ferromagnetic layer in magnetoresistive sensor applications, by reducing the coercivity and/or improving the reversibility. We have used it in the design of our new magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…28 Better values of field detectivity have only obtained in this way. [29][30][31][32] For example, Chaves et al have reported a value of field detectivity of 51 pT= ffiffiffiffiffiffi Hz p at 30 Hz and field sensitivity of 870%/ mT by using a flux concentrator. 29,30 The relation of magnetic field, field sensitivity, and field detectivity is plotted in Figure 4(b).…”
mentioning
confidence: 99%
“…28 Better values of field detectivity have only obtained in this way. [29][30][31][32] For example, Chaves et al have reported a value of field detectivity of 51 pT= ffiffiffiffiffiffi Hz p at 30 Hz and field sensitivity of 870%/ mT by using a flux concentrator. 29,30 The relation of magnetic field, field sensitivity, and field detectivity is plotted in Figure 4(b).…”
mentioning
confidence: 99%
“…The inclusion of NiFe directly after CoFeB strongly reduces TMR due to the texture propagation from NiFe (fcc 1 1 1) to CoFeB (bcc 1 0 0) [61]. Correct crystallography can be assured introducing a thin Ta dusting layer (∼0.21 nm) between these layers.…”
Section: Choice Of Electrode Materials For Tmr Sensorsmentioning
confidence: 99%
“…The fabrication of these MTJ was done as follows: First, a multilayer stack was deposited onto a thermally oxidized silicon substrate in a magnetron sputtering system with a base pressure of 5 Â 10 MgO insulator comprise the free layer, and the three layers below are part of the synthetic antiferromagnetic (SAF) reference layer [26]. Optical lithography was used to pattern a chain of ten 40 Â 10 μm MTJ ellipses with each major axis aligned along the chain length.…”
Section: Reading Informationmentioning
confidence: 99%